Orsaker till säsongsvariation av arsenik i Lillesjön - Areskog, Jacob (SLU/Dept. of Soil and Environment, 2016)
Sweden has established 16 environmental quality objectives to attain a sustainable development, one of them is A Non-Toxic Environment. The county administrative board of Jönköping is working together with Nässjö county in harmony with the directions from the environmental quality objective to remediate the contaminated area in Grimstorp, Nässjö county. The contamination erupts from a wood preserva-tion operation whereas the use of toxic substances such as arsenic and polycyclic aromatic hydrocarbons has severely contaminated the soil. Large amounts of arse-nic have found its way to the closely situated Lillesjön. The arsenic content of the lake water is displaying a yearly seasonal pattern with the highest concentrations, around 8 µg/L, in August and September. Nässjö county has proposed to biomanipulate the lake in order to reduce the resuspension of arsenic containing sediments. The objective of this bachelor thesis is to investigate, through literature and measurements of parameters in Lillesjön during March 2010 to December 2011, if there is an alternative or additional mechanism to resuspension that is causing the release and seasonal pattern of arsenic in Lillesjön. Covariance and positive significant correlations were found between arsenic-iron, arsenic-manganese and arsenic-phosphorus, which together with measured oxygen-saturation in the lake, implies an anaerobic mechanism for the release and seasonal variation of arsenic in Lillesjön. No significant correlations were found between turbidity and other parameters which implies that the water’s clarity, and thus the particle content, was not related to the arsenic content of the water. Before the assessed biomanipulation an experimental set-up with sediment samples from Lillesjön incubated under differing chemical conditions should be executed in order to confirm an anaerobic release mechanism of arsenic.